Turbo spin non echo-planar diffusion weighted MRI for cholesteatoma in revision mastoidectomy: a prospective study of diagnostic accuracy and clinical impact - Paddle, Paul; Hurtado, Guillermo; Goergen, Stacy; Hong, Sharon; Baxter, Malcolm; Copson, Bridget (Australian Journal of Otolaryngology; Vol 1 (March 2018): Australian Journal of Otolaryngology, 2018)
Background: Non-echo planar diffusion weighted MRI (NEDWI MRI) is accurate in detecting cholesteatoma in the post-operative ear but the effect on surgical decision-making in the setting of revision mastoid surgery using surgical histopathology as the gold standard has not been investigated. Methods: A blinded diagnostic accuracy study of pre-operative NEDWI MRI was conducted for consecutive patients requiring revision mastoid surgery. The operating surgeon completed a pre-operative survey without knowledge of the MRI results and post-operative survey after knowledge of the MRI results to determine impact on clinical decision making. Results: Non-EPI DWI MRI demonstrated overall sensitivity of 45.45% (95% CI: 16.75–76.62), specificity of 88.24% (95% CI: 63.56–98.54%), in detecting recurrent cholesteatoma in 28 operations. In 65.22% of cases the operating surgeon would have proceeded with second look surgery regardless of the MRI result. Conclusions: Negative NEDWI has the potential to reduce unnecessary surgery in patients who have no indication for surgery other than disease surveillance.